The effect of water loading on acute weight loss following fluid restriction in combat sports athletes - Reale, R.; Slater, G.; Cox, G. R.; Dunican, I. C.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Novel methods of acute weight loss practiced by combat sport athletes include "water loading," the consumption of large fluid volumes for several days prior to restriction. We examined claims that this technique increases total body water losses, while also assessing the risk of hyponatremia. Male athletes were separated into control (n = 10) and water loading (n = 11) groups and fed a standardized energy-matched diet for 6 days. Days 1-3 fluid intake was 40 and 100 ml/kg for control and water loading groups, respectively, with both groups consuming 15 ml/kg on Day 4 and following the same rehydration protocol on Days 5 and 6. We tracked body mass (BM), urine sodium, urine specific gravity and volume, training-related sweat losses and blood concentrations of renal hormones, and urea and electrolytes throughout. Physical performance was assessed preintervention and postintervention. Following fluid restriction, there were substantial differences between groups in the ratio of fluid input/output (39%, p < .01, effect size = 1.2) and BM loss (0.6% BM, p = .02, effect size = 0.82). Changes in urine specific gravity, urea and electrolytes, and renal hormones occurred over time (p < .05), with an interaction of time and intervention on blood sodium, potassium, chloride, urea, creatinine, urine specific gravity, and vasopressin (p < .05). Measurements of urea and electrolyte remained within reference ranges, and no differences in physical performance were detected over time or between groups. Water loading appears to be a safe and effective method of acute BM loss under the conditions of this study. Vasopressin-regulated changes in aquaporin channels may potentially partially explain the mechanism of increased body water loss with water loading.